2021
DOI: 10.3389/fimmu.2021.657363
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Type I Interferon Levels and COVID-19 Severity: A Systematic Review and Meta-Analysis

Abstract: IntroductionCoronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, resulting in a range of clinical manifestations and outcomes. Laboratory and immunological alterations have been considered as potential markers of disease severity and clinical evolution. Type I interferons (IFN-I), mainly represented by IFN-α and β, are a group of cytokines with an important function in antiviral responses and have played a complex role in COVID-19. Some studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 99 publications
3
31
0
Order By: Relevance
“…Though inborn genetic errors in type I IFN pathway and neutralizing antibodies against type I IFNs leading to impaired type I IFN responses have been associated with adverse outcomes in the setting of SARS-CoV-2 infection ( 43 45 ), in the present study we did not detect a direct association between type I IFN peripheral blood score and adverse outcomes such as intubation risk or death. This observation is in accord with a recent meta-analysis by da Silva et al reporting that plasma protein levels of type I IFN cannot be used as a severity marker for COVID-19 ( 46 ). Besides, activation of type I IFN pathway has been previously shown to upregulate the expression of angiotensin converting enzyme-2 receptors in a loop-back mechanism, resulting in further augmentation in intracellular viral load in COVID-19 disease ( 47 ).…”
Section: Discussionsupporting
confidence: 90%
“…Though inborn genetic errors in type I IFN pathway and neutralizing antibodies against type I IFNs leading to impaired type I IFN responses have been associated with adverse outcomes in the setting of SARS-CoV-2 infection ( 43 45 ), in the present study we did not detect a direct association between type I IFN peripheral blood score and adverse outcomes such as intubation risk or death. This observation is in accord with a recent meta-analysis by da Silva et al reporting that plasma protein levels of type I IFN cannot be used as a severity marker for COVID-19 ( 46 ). Besides, activation of type I IFN pathway has been previously shown to upregulate the expression of angiotensin converting enzyme-2 receptors in a loop-back mechanism, resulting in further augmentation in intracellular viral load in COVID-19 disease ( 47 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, a recent meta-analysis by Silva et al. ( 24 ), which included 15 studies examining the plasma protein levels of IFN-I (α and β), could not confirm a significant association between plasma IFN- I levels and COVID-19 disease severity. In the included studies, IFN-α was measured over 7 days after the onset of symptoms ( 25 32 ), and IFN-α levels at the early phase of SARS-CoV-2 infection (within 5 days after the onset of symptoms) were assessed only in one study ( 30 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, despite the likely protective role of IFN, data are still conflicting regarding the association between IFN levels and the outcome of SARS-CoV-2 infection. A recent meta-analysis on circulating IFNα in COVID-19 patients concluded that peripheral IFNα cannot be used as a severity marker [16]. In fact, the outcome relies not only on IFNα levels but also on other factors such as the timing of production.…”
Section: Discussionmentioning
confidence: 99%